On the road to per cent accuracy – II. Calibration of the non-linear matter power spectrum for arbitrary cosmologies. Issue 4 (21st September 2019) - Giblin, Benjamin; Cataneo, Matteo; Moews, Ben; Heymans, Catherine
ABSTRACT: We introduce an emulator approach to predict the non-linear matter power spectrum for broad classes of beyond-ΛCDM cosmologies, using only a suite of ΛCDM N -body simulations. By including a range of suitably modified initial conditions in the simulations, and rescaling the resulting emulator predictions with analytical 'halo model reactions', accurate non-linear matter power spectra for general extensions to the standard ΛCDM model can be calculated. We optimize the emulator design by substituting the simulation suite with non-linear predictions from the standard halofit tool. We review the performance of the emulator for artificially generated departures from the standard cosmology as well as for theoretically motivated models, such as f ( R ) gravity and massive neutrinos. For the majority of cosmologies we have tested, the emulator can reproduce the matter power spectrum with errors ${\lesssim}1{{\ \rm per\ cent}}$ deep into the highly non-linear regime. This work demonstrates that with a well-designed suite of ΛCDM simulations, extensions to the standard cosmological model can be tested in the non-linear regime without any reliance on expensive beyond-ΛCDM simulations.